Дослідження можливостей ефективного застосування для операцій доведення шліфпорошків з композиційних кубонітових компактів - Лавріненко, В.І.; Богатирьова, Г.П.; Нікітін, Ю.І.; Петасюк, Г.А.; Лєщук, І.В.; Пасічний, О.О.; Ситник, Б.В.; Полторацький, В.Г. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Results of carrying out of a complex of research works by definition physicomechanical and morphological properties of the developed mixes and their initial conditions. Results of test in grinding circles of powders with a different parity of a standard micropowder SNB KM 40/28 and grinding micropowder from composite CNB compact.